Ang madyik ni Paolo Paolo's magic - Oris, Glenda Callanta; Tejido, Jomike; Bravo, Becky (Quezon City Lampara Publishing House, Inc., 2013)
"Paolo does not like having haircut. He has too many reasons not to. But it cannot be possible that he does not get a haircut. What should be done? Find out in this story how in the end Paolo had his hair cut, and how being creative can help in solving small everyday problems, like visiting the barbershop."
Stories with moral values
Text in Filipino and English.
Don Carlos Palanca awards for literature, ikalawang gantimpala, maikling kuwentong pambata 2001.
Keywords: Haircutting -- Fiction